Randomised controlled trial of an occupational therapy intervention to increase outdoor mobility after stroke. Issue 7479 (25th November 2004) - Logan, P A; Gladman, J R F; Avery, A; Walker, M F; Dyas, J; Groom, L
Abstract: Objective To evaluate an occupational therapy intervention to improve outdoor mobility after stroke. Design Randomised controlled trial. Setting General practice registers, social services departments, a primary care rehabilitation service, and a geriatric day hospital. Participants 168 community dwelling people with a clinical diagnosis of stroke in previous 36 months: 86 were allocated to the intervention group and 82 to the control group. Interventions Leaflets describing local transport services for disabled people (control group) and leaflets with assessment and up to seven intervention sessions by an occupational therapist (intervention group). Main outcome measures Responses to postal questionnaires at four and 10 months: primary outcome measure was response to whether participant got out of the house as much as he or she would like, and secondary outcome measures were response to how many journeys outdoors had been made in the past month and scores on the Nottingham extended activities of daily living scale, Nottingham leisure questionnaire, and general health questionnaire. Results Participants in the treatment group were more likely to get out of the house as often as they wanted at both four months (relative risk 1.72, 95% confidence interval 1.25 to 2.37) and 10 months (1.74, 1.24 to 2.44). The treatment group reported more journeys outdoors in the month before assessment at both four months (median 37 in intervention group, 14 in control group: P < 0.01) and 10 months (median 42 in intervention group, 14 in control group: P < 0.01). At four months the mobility scores on the Nottingham extended activities of daily living scale were significantly higher in the intervention group, but there were no significant differences in the other secondary outcomes. No significant differences were observed in these measures at 10 months. Conclusion A targeted occupational therapy intervention at home increases outdoor mobility in people after stroke.